MAKNA JASA PINJAMAN DALAM UNIT USAHA SIMPAN PINJAM - Alif Ilham Akbar Fatriansyah; Iwan Triyuwono; Roekhudin Roekhudin (Jurnal Ekonomi dan Bisnis, 2018)
This study aims at understanding the meaning of the loan in the loan business services basedon the members’ perceptions of Eko Kapti cooperative. This study uses TranscendentalPhenomenology approach by Edmund Husserl. The results of this study show that the “the loanservices are the results of inconsistencies in the use of a principle”, whether using syariah orconventional principles, so that the existing loan business services are considered as part ofsyariah containing usury.Keywords: Understanding the meaning of the loan services, Cooperatives, Inconsistency,Syariah or Conventional